STRATEGI PEMENANGAN PASANGAN ANNAS MAAMUN DAN ARSYAD JULIANDI RACHMAN PADA PEMILIHAN GUBERNUR DAN WAKIL GUBERNUR RIAU PUTARAN KE DUA DI KUANTAN SINGINGI TAHUN 2013 - Jefy Faizal; Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The election of Governor and Deputy Governor of Riau in 2013 first round in Kuantan Singingi pair Annas Maamun and Arsyad Juliandi Rachman gain sound that is 12 % of the votes of five pairs of candidates. And in the second round managed to improve his voice acquisition of 50,6 % of two pairs of candidats. This shows the success of the winning team seize voters, especially voters supporters of candidater for Governor and Deputy Governor of Riau who lost in the first round. Therefor, this study was conducted to determine the strategies used winning team pair Annas Maamun and Arsyad Juliandi Rachman the second round of elections for Governor and Deputy Governor of Riau year 2013.The type of research using descriptive qualitative methods and research sites in Kuantan Singingi. Informants in this study consisted of a winning team pair Annas Maamun and Arsyad Juliandi Rachman and community leaders with data collection through direct interviews and documentation.The results showed that the winning strategy pair Annas Maamun and Arsyad Juliandi Rachman on the election of Governor and Deputy Governor of the second round in Kuantan Singingi year 2013 by way : 1. Political Communication, 2. Mobilitation, 3. Chasing, 4. Push Marketing, 5. Pass Marketing, 6. Pull Marketing. The impact of these strategies on sound acquisition pair Annas Mamun and Arsyad Juliandi Rachman is the rising number of votes pair Annas Maamun and Arsyad Juiandi Rachman is the rising number of votes and the second round in Kuantan Singingi from 12 % to 50,6 % of the vote. The recapitulation of the second round of vote counting showed that pair Annas Maamun and Arsyad Juliandi Rachman won the guvernatorial candidate pairs supporting voice Riau especilly who lost in the first round.Keyword : Political strategy, political marketing, the winning team.